Odpowiedzi

2010-01-10T11:37:36+01:00
=
3x+6+2y-4=1x+2-4y+4=1
x-4y=-5 /×-3
3x+2y=-1
-3x+12y=15
3x+2y=-1
14y=14
y=1

x-4×1=-5
x=-5+4
x=-1
Najlepsza Odpowiedź!
2010-01-10T11:40:16+01:00
3x+6+2y-4=1
x+2-4y+4=1

2y=-3x-6+4+1
x=-2+4y-4+1


2y=-3x-1 /:2
x=4y-5

y=-15x-0,5
x=4y-5


y=-1,5*(4y-5)-0,5
x=4y-5


y=-6+7,5-0,5
x=4y-5

y=1
x=-1
2010-01-10T12:34:01+01:00
3x + 6 + 2y - 4 = 1
x + 2 - 4y + 4 = 1

3x + 2y = 1 + 4 - 6
x - 4y = 1 -4 - 2

3x + 2y = -1/*2
x -4y = -5

6x +4y = -2
x - 4y = -5

7x = -7 /:7
x= -1

x - 4y = -5
-1 - 4y = -5
-4y = -5 +1
-4y = -4 /: (-4)
y = 1

Odp X = -1, y = 1